(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article was born as a result of a research financed within the framework of the Internal Call 001 - 2017 for the Financing of Research and Development Projects of the Technological Institution Colegio Mayor de Bolívar and is part of the macro-project “Social Restoration as a Tool for the Action without Harm and Peacebuilding, after the Armed Conflict in Colombia ”. Objective: Describe the incidence of the effects of the armed conflict and the peace accords in the social restoration of victims and displaced persons in seven (7) municipalities of the Colombian Caribbean Coast, promoting the implementation of actions for their integral reparation, as part of the dynamics of the post-agreements. Material and Method: The study was carried out with a qualitative approach, from an exploratory-descriptive research, which will recognize the social, demographic, cultural and economic characteristics of the victims of the armed conflict in the municipalities of Tuchín (Córdoba), Chalán (Sucre) ), Carmen de Bolívar (Bolívar), Santa Lucía (Atlántico), Ariguaní (Magdalena), Bosconia (Cesar) and Villanueva (Guajira). Consistent with the investigative approach and according to Passos (2015), it was determined “a part of the population, sufficiently necessary to obtain the required information” (Therefore, a probabilistic sample was worked, stratified at random and for convenience, since each element could be determined the possibility of forming part of the sample in question (p. 24, 25); in the sense of the above it was necessary to determine a stratified sample proportional to random of 1% of the total inhabitants of the municipalities of the seven selected departments whose approximate universe is 227,887, leaving a population of 2,278 and a convenience sample of 340 inhabitants of the Colombian Caribbean affected by the violence. Referring to conflict, unfailingly leads us to think about an undeniable reality that Colombia has been going through for more than five decades; This article shows an investigative phase that reports the results of the impact that the peace accords have had on the aforementioned municipalities; evidencing that the population victim of the armed conflict, expressed their refusal to the Peace Agreement, since they feel that they were not taken into account in the construction of such a transcendental agreement, not only for the region, but also for the country and for Latin America. . On the other hand, there are those who, if they approve the agreement, but consider that there could be better, if it had contemplated their positions vis-à-vis the process as such; Likewise, one found a minority that showed their total and absolute agreement, arguing that it is the best way to end this scourge. Likewise, 80% of those surveyed stated that after the signing of the aforementioned agreement, there has not been a positive development regarding security on the Caribbean Coast, with 10% of the population saying that they have seen slight progress. in security aspects. In addition to the fact that the vast majority of the population object of the investigation stated that they did not show positive aspects regarding security in the regions, special emphasis was placed on the increase in insecurity, because although the agreement implied the end After the war, illegal groups are also identified by appropriating some territories, as well as dissidents from the peace process. This is how the majority of respondents consider that security on the Caribbean coast is considered that the impact of the signing of the agreement has not changed the harsh reality marked by the violence of social conflicts that permeates the territories and even more the expression of sentiment of bewilderment and laziness about what they consider continues to be the lack of protection of the State. In summary, the municipalities that are the object of the investigation have been the most affected by the armed conflict in the Caribbean region, since for many years they were the epicenter of combats between the FARC and the paramilitaries; coupled with the governmental neglect of both the national and territorial order and that despite the signing of the agreement, they continue to feel abandoned by the State.